Situational Action Theory and the particular case of settings including a group - Kleinewiese, Julia (European journal of criminology, 2022)
Situational Action Theory (SAT) postulates that personal crime propensity and the setting?s criminogenic features are direct causes of crime. This perspective also places a central focus on the moral factors involved. The moral norms of settings have not yet been exhaustively examined in regard to the aspects that may influence them. This theoretical article applies SAT to the particular case of settings including a group. Building upon previous literature on social cohesion in groups (such as team spirit/esprit de corps), the group present in the setting is presumably more likely to be identified by the individual if such group cohesiveness is high. When perceived, the moral norms of the group and deterrence should have an influence through becoming part of the setting in the causation of crime, according to SAT. This application suggests that SAT is a fruitful approach for explaining the impacts of groups on crime.